1989
DOI: 10.1111/j.1651-2227.1989.tb17940.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Pattern of Cerebral Palsy in the Southwest Region of Finland

Abstract: The prevalence of cerebral palsy (CP) increased significantly from 1968-72 to 1978-82 in the region of the University Central Hospital of Turku, Finland, from 1.6/1,000 live births during the first five-year period to 2.5/1,000 live births during the second. The increase was due to an increase of CP in low birthweight children (p = 0.0002). The distribution of CP patterns did not change significantly. During the second period the diagnosis was made earlier in all groups (except that of spastic tetraplegia), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 12 publications
10
29
1
3
Order By: Relevance
“…The logical consequence would be an increasing occurrence of CP in the population of low birth weight infants, and possibly also in the total population. In fact several investigations have shown this to be the case [3,5,7,12,14,15]. Experiences from our population during the 15-year-period 1970-84, however, were more in accordance with the first mentioned statement [9].…”
Section: Introductionsupporting
confidence: 69%
“…The logical consequence would be an increasing occurrence of CP in the population of low birth weight infants, and possibly also in the total population. In fact several investigations have shown this to be the case [3,5,7,12,14,15]. Experiences from our population during the 15-year-period 1970-84, however, were more in accordance with the first mentioned statement [9].…”
Section: Introductionsupporting
confidence: 69%
“…From 8 international centres, consistent evidence has emerged of an increase in cerebral palsy (CP) during childhood, data of six of these are summarized in Figure l ( 3, 6, 15,16,18,19). Over the last 30 years there has been no distinct change in the incidence of CP in infants bora at term, whereas the incidence of CP in preterm infants initially decreased uptil the 70's but has increased thereafter.…”
Section: Cerebral Palsy Increasesmentioning
confidence: 97%
“…l 197Ο 1975Fig. l 198Ο 1985 year Trends in incidence of cerebral palsy per 1000 live births in regions in Denmark (6), Sweden (6), Finland (16), England (15), Ireland (3) and Japan (19).…”
Section: Cerebral Palsy Increasesmentioning
confidence: 99%
“…If an initial rise and subsequent fall in very preterm cerebral palsy rates is a general phenomenon with the refinement of NIC techniques, it may explain the diversity of published effects of NIC on cerebral palsy rates in immature infants, if the time points compared lie at different points of the NIC learning curve. Thus, from both Victoria, Australia [Victorian Infant Collaborative Study, 1991] and Ontario, Canada [Saigal et al, 1989], decreased cerebral palsy rates in infants of ,1,000 g were reported between the late 1970s and the early 1980s, while in southwest Finland the cerebral palsy rate of infants of ,2,500 g increased between 1968-1972and 1978[Riikonen et al, 1989. These results are compatible with similar experiences in all three places if NIC were introduced during the 1970s, creating an initial increase and subsequent decrease in very preterm cerebral palsy rates.…”
Section: Cerebral Palsy and Maturity At Birthmentioning
confidence: 99%